Analyze on character motivation of road movie - Mohd Azzaini, bin Mohd Akil (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study ia to identify the characters motivation of the road movies. Element of roads, vehicle and adventure was make the road movies seem different htan other films genre. The protagonist's character in the road movies will move away his lofe to be on the road. However, there has been no clear resources weter underlines the character movtivation in the road movies. To identify the character motivation in the road movies clearly, content analysis and qualitative methods were used. Ten kind of road movie come from different countries and year were analyzed. Findings of the study, was applied to the shor video titled "Bahu Kiri". Premise of this film is about religion, famliy and companions is a top priority.